Email meets issue-tracking: a prototype implementation - Kwinana, Zukhanye N (Rhodes University, Faculty of Science, Department of Computer Science, 2006)
The use of electronic mail (email) has evolved from sending simple messages to task delegation and management. Most mail clients, however, have not kept up with the evolution and as a result have limited task management features available. On the other hand, while issue tracking systems offer useful task management functionality, they are not as widespread as emails and also have a few drawbacks. This thesis reports on the exploration of the integration of the ubiquitous nature of email with the task management features of issue-tracking systems. We explore this using simple ad-hoc as well as semi-automated tasks. With these two working together, tasks can be delegated from email clients without needing to switch between the two environments. It brings some of the benefits of issue tracking systems closer to our email users.The system is developed using Microsoft VisuaI Studio.NET. with the code written in C#. The eXtreme Programming (XP) methodology was used during the development of the proof-of-concept prototype that demonstrates the integration of the two environments, as we were faced at first with vague requirements bound to change, as we better understood the problem domain through our development. XP allowed us to skip an extended and comprehensive initial design process and incrementally develop the system, making refinements and extensions as we encountered the need for them. This alleviated the need to make upfront decisions that were based on minimal knowledge of what to expect during development. This thesis describes the implementation of the prototype and the decisions made with each step taken towards developing an email-based issue tracking system. With the two environments working together, we can now easily track issues from our email clients without needing to switch to another system.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Microsoft Visual studio; Electronic mail systems; Computer networks; eXtreme programming; Computer software -- Development